Barrier Island Sediments Reveal Storm Surge and Fluvial Flood Events in the Past Centuries at Thua Thien Hue, Central Vietnam - Kongsen, Stapana; Phantuwongraj, Sumet; Choowong, Montri; Chawchai, Sakonvan; Chaiwongsaen, Nikhom; Fuengfu, Supawich; Vu, Doan Thi Anh; Tuan, Dinh Quoc; Preusser, Frank (Frontiers in Ecology and Evolution, 2021)
Sedimentary evidence of storms and fluvial floods (FFs) is crucial for a better understanding of such events in coastal zones. In this study, we analyzed the sedimentary characteristics of the coastal storm and FF deposits at the Hoa Duan barrier, Thua Thien Hue, central Vietnam. Analyses of the sedimentary structures and properties (grain size distribution, composition, roundness, and sphericity) and loss on ignition revealed that the storm sediments were comprised of coarser grains with a low organic and carbonated content, and with sedimentary structures, including parallel and inclined landward lamination, multiple sets of normal and reverse grading, mud rip-up clasts, and sharp and erosional contacts (both top and bottom) with finer-grain layers. Conversely, the FF sediments had only fine to very fine grains, with dominant high organic and carbonate contents, and only exhibited sedimentary structures of sharp erosional top and bottom contacts with coarser-grained layers. The clearest differentiation to distinguish coastal storm layers from inland FF layers was obtained by plotting the mean grain size against the sorting. The results of optically stimulated luminescence dating suggested that two storms layers and one FF layer were deposited during the last 130 ± 10 years. Moreover, two layers were deposited by storms and one by a FF prior to that (> 130 ± 10 years). The identification of the sedimentary diagnostic key of these two hazards can help to improve the understanding of the geomorphological evolution of the studied site and the other parts of this coastal region in order to remind the coastal community to prepare for the future coastal hazards well.